2018
DOI: 10.1101/504274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensorimotor conflicts alter perceptual and action monitoring

Abstract: 142)1 Bodily self-consciousness is defined as a set of prereflective representations of integrated bodily 2 signals giving rise to self-identification, self-location and first-person perspective. While bodily self-3 consciousness is known to modulate perception, little is known about its influence on higher-level 4 cognitive processes. Here, we manipulated bodily self-consciousness by applying sensorimotor 5 conflicts while participants performed a perceptual task followed by confidence judgments. Results 6 sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…This study sits within a growing body of literature which shows associations between action-related information and metacognitive judgements (Faivre et al, 2018(Faivre et al, , 2020Fleming et al, 2015;Palser et al, 2018;Pereira et al, 2020;Siedlecka, Hobot, et al, 2019;Siedlecka et al, 2020;Wokke et al, 2020). By directly manipulating the amount of effort required to report a decision we have shown that confidence depends, in part, on fine-grained representations of one's own actions.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This study sits within a growing body of literature which shows associations between action-related information and metacognitive judgements (Faivre et al, 2018(Faivre et al, , 2020Fleming et al, 2015;Palser et al, 2018;Pereira et al, 2020;Siedlecka, Hobot, et al, 2019;Siedlecka et al, 2020;Wokke et al, 2020). By directly manipulating the amount of effort required to report a decision we have shown that confidence depends, in part, on fine-grained representations of one's own actions.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this view, a number of studies have provided evidence that actionrelated information can indeed affect perceptual confidence judgements (Faivre, Filevich, Solovey, Kühn, & Blanke, 2018;Faivre et al, 2020;Fleming et al, 2015;Palser, Fotopoulou, & Kilner, 2018;Pereira et al, 2020;Siedlecka, Hobot, et al, 2019;Siedlecka, Paulewicz, & Koculak, 2020;Wokke, Achoui, & Cleeremans, 2020). For example, Fleming and colleagues (2015) applied single-pulse TMS to the dorsal premotor cortex before and after responses during a visual discrimination task.…”
Section: Introductionmentioning
confidence: 97%
“…This study sits within a growing body of literature which shows associations between action-related information and metacognitive judgements (Faivre et al, 2018(Faivre et al, , 2020Fleming et al, 2015;Palser et al, 2018;Pereira et al, 2020;Siedlecka, Hobot, et al, 2019;Siedlecka et al, 2020;Wokke et al, 2020). By directly manipulating the amount of effort required to report a decision we have shown that confidence depends, in part, on fine-grained representations of one's own actions.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with this view, a number of studies have provided evidence that actionrelated information can indeed affect perceptual confidence judgements (Faivre, Filevich, Solovey, Kühn, & Blanke, 2018;Faivre et al, 2020;Fleming et al, 2015;Palser, Fotopoulou, & Kilner, 2018;Pereira et al, 2020;Siedlecka, Hobot, et al, 2019;Siedlecka, Paulewicz, & Koculak, 2020;Wokke, Achoui, & Cleeremans, 2020). For example, Fleming and colleagues (2015) applied single-pulse TMS to the dorsal premotor cortex before and after responses during a visual discrimination task.…”
Section: Introductionmentioning
confidence: 97%
“…The link between confidence and trajectories in the control group corroborates the view that sensorimotor signals shape confidence estimates. Indeed, previous studies showed that electromyographic activity (Gajdos, Fleming, Saez Garcia, Weindel, & Davranche, 2019) and alpha power over somatosensory scalp regions (Faivre, Filevich, Solovey, Kuhn, & Blanke, 2018) covary with confidence, and that altering sensorimotor signaling by increasing movement speed (Palser, Fotopoulou, & Kilner, 2018) or by inducing sensorimotor conflicts (Faivre, Vuillaume, et al, 2019) disrupt metacognitive accuracy. The weaker link between trajectories and confidence in schizophrenia may be related to slower and noisier motor behavior, or to the tendency of patients to neglect relevant internal cues to control motor actions (Frith, Blakemore, & Wolpert, 2000) .…”
Section: Relationships Between Action Execution and Metacognitive Permentioning
confidence: 99%